Peri‐operative risk factors for delayed gastric emptying after a pancreaticoduodenectomy. Issue 6 (28th February 2015) - Robinson, Jamie R.; Marincola, Paula; Shelton, Julia; Merchant, Nipun B.; Idrees, Kamran; Parikh, Alexander A.
Abstract Background Delayed gastric emptying (DGE) is a frequent cause of morbidity, prolonged hospital stay and readmission after a pancreaticoduodenectomy (PD). We sought to evaluate predictive peri‐operative factors for DGE after a PD. Methods Four hundred and sixteen consecutive patients who underwent a PD at our tertiary referral centre were identified. Univariate and multivariate (MV) logistic regression models were used to assess peri‐operative factors associated with the development of clinically significant DGE and a post‐operative pancreatic fistula (POPF). Results DGE occurred in 24% of patients (n = 98) with Grades B and C occurring at 13.5% (n = 55) and 10.5% (n = 43), respectively. Using MV regression, a body mass index (BMI) ≥35 [odds ratio (OR) = 3.19], operating room (OR) length >5.5 h (OR = 2.72) and prophylactic octreotide use (OR = 2.04) were independently associated with an increased risk of DGE. DGE patients had a significantly longer median hospital stay (12 versus 7 days), higher 90‐day readmission rates (32% versus 18%) and an increased incidence of a pancreatic fistula (59% versus 27%). When controlling for POPF, only OR length >5.5 h (OR 2.73) remained significantly associated with DGE. Conclusions DGE remains a significant cause of morbidity, increased hospital stay and readmission after PD. Our findings suggest patients with a BMI ≥35 or longer OR times have a higher risk of DGE either independently or through the development of POPF. These patients should be considered for possible enteral feeding tube placement along with limited octreotide use to decrease the potential risk and consequences of DGE.